Optimizing Organizational Performance Through a Conversation-Based Performance Management System Approach - Tati Ariaini; Aryana Satrya (PT Mattawang Mediatama Solution, 2024)
This study examines the need for an effective performance management system within organizations. Prior research indicates that such systems significantly enhance business outcomes (Pulakos, Mueller-Hanson & Arad, 2019). O’Kane, McCracken & Brown (2022) introduced a conversation-based performance management model grounded in social exchange theory (SET), suggesting that discussions between supervisors and subordinates foster positive reciprocal relationships. This research aims to analyze the effectiveness of the performance management system implemented by a private trading company in Indonesia. The qualitative study involved semi-structured interviews with the Board of Directors, HRD, Line Managers, and Staff, as well as focus group discussions with Senior Managers. Findings reveal gaps in the system's implementation, notably the absence of feedback processes central to this model. Identified factors contributing to these gaps include goal alignment, feedback frequency, skills development, and formality, alongside environmental factors such as design, development function, buy-in, culture, and linkage with other systems. The study underscores the importance of feedback and explores the system's effectiveness from various perspectives, offering insights that contribute to the literature on performance management systems, particularly conversation-based approaches in private companies in Indonesia.